Rewriting the two equations:
[Supply] [tex]p = q^2+20[/tex]
[Demand] [tex]p=-4q^2+10q+18600[/tex]
Equilibrium price is when
Supply = Demand
[tex]q^2+20 = -4q^2+10q+18600[/tex]
[tex]q^2+4q^2+20-10q-18600 = 0[/tex]
[tex]5q^2-10q-18580=0[/tex] ⇒ Simplifying the equation by dividing each term by 5
[tex]q^2-2q-3716=0[/tex]
The simplified equation is in quadratic form.
There are three main methods for solving a quadratic equation: factorizing, completing the square, or quadratic formula.
Using the formula, we need the value of a, b, and c which is the constant of the quadratic equation.
[tex]q_1= \frac{-b+ \sqrt{(b)^2-4ac)} }{2a} [/tex], and [tex]q_2= \frac{-b- \sqrt{(b)^2-4ac)} }{2a} [/tex]
We have a = 1, b = -2, and c = -3716
Substituting these values into the formula we have
[tex]q_1= \frac{-(-2)+ \sqrt{(-2)^2-4(1*-3716)} }{2} =61.97[/tex]
[tex]q_2= \frac{-(-2)- \sqrt{(-2)^2-4(1*-3716)} }{2} =-59.97[/tex]
Since 'q' represents a quantity, we can't have negative values, so we choose the value of 'q' to be 61.97 ≈ 62 (rounded to the nearest whole number)
Answer: Equilibrium quantity = 62